2007
DOI: 10.1002/hbm.20455
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study on memory discriminability for complex visual scenes

Abstract: The fan effect represents an increase in reaction time for the recognition of an item as a function of the amount of information associated with that item in memory. The present study used fMRI to study the neural correlates of the fan effect for complex visual scenes. We used a test in which landscape pictures were divided vertically into three equal segments. In the high discriminability condition only one segment was presented during encoding, whereas in the low discriminability condition two different segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the current experiment we used complex scene stimuli including both outdoor scenes as well as scenes of animals. The visual scene stimuli in particular have been shown to be highly effective at engaging the hippocampus in humans (Stern et al 1996;Hartley et al 2007;Blondin and Lepage 2007). Using these stimuli, we report that 90% of the hippocampal cells were responsive to the location-scene task and 73% of those responsive cells were selective.…”
Section: Sustainedmentioning
confidence: 88%
“…In the current experiment we used complex scene stimuli including both outdoor scenes as well as scenes of animals. The visual scene stimuli in particular have been shown to be highly effective at engaging the hippocampus in humans (Stern et al 1996;Hartley et al 2007;Blondin and Lepage 2007). Using these stimuli, we report that 90% of the hippocampal cells were responsive to the location-scene task and 73% of those responsive cells were selective.…”
Section: Sustainedmentioning
confidence: 88%
“…Reduced activation of the right lingual gyrus and cuneus during criticism relative to neutral comments may suggest lesser use during criticism of autobiographical (Burianova and Grady 2007) and visual memory (Blondin and Lepage 2008), recognition of facial affect (Kitada et al 2010) and verbal affect (Rama et al 2001), as well as lesser use of mental imagery during affect recognition (Kim et al 2007) that are normally associated with these brain regions. During neutral comments which consisted of describing the participant ' s general day-to-day activities (see Supplementary text available online), such as going shopping, as well as specifi c recent activities, such as going on holiday, information may be processed in a relatively non-affective way, such as recollection of gyrus, another cluster located in the left claustrum, extending to the putamen and subthalamic nucleus of the brain stem, a cluster located in the right inferior occipital gyrus, extending to the right lingual gyrus and right fusiform gyrus, a cluster in the right thalamus and right insula, and clusters in the right precentral gyrus and right medial frontal gyrus, extending to the middle frontal gyrus (Table V and Figure 1).…”
Section: Increased Activation Of Left Superior and Middle Frontal Gyrmentioning
confidence: 99%
“…Specifically, several works have tried to conceptualize a theoretical framework for interference-mediated forgetting [ 2 ] and attempted to dissect the physiological variables and molecular mechanisms underlying forgetting and interference dynamics [ 5 ]. At the circuit level, interference involves multiple brain regions that are necessary for memory storage and retrieval [ 6 , 7 , 8 ]. It has been shown that, in the novel object recognition (NOR) paradigm, exposure to an interference session during the consolidation phase leads to memory loss, and this effect is dependent on medial prefrontal cortex and hippocampal activity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%